IMPROVING THE METHODS OF DEVELOPING PREVENTIVE COMPETENCIES OF STUDENTS BASED ON A CREATIVE APPROACH - Dalimova Shoira Kasimdjanovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In the context of modern education, the formation of preventive competencies among students has become an essential pedagogical task, especially in medical, pedagogical, and social sciences. These competencies refer to the ability of future professionals to anticipate, identify, and mitigate risks to health, safety, and well-being in both personal and professional contexts. A creative approach to their development involves non-standard, problem-solving, and student-centered strategies that foster initiative, reflection, and responsibility. The relevance of the topic is driven by the increasing complexity of social and health-related challenges, which require young specialists to act not only reactively but also proactively. In traditional curricula, preventive training is often limited to theoretical awareness. However, international pedagogical practice increasingly emphasizes competency-based education, where knowledge is operationalized into practical readiness. Thus, there is a growing need to modernize teaching methods so they not only transmit information but also stimulate students’ creative thinking and self-regulation in risk prevention.